Finding PASSION by DOing the things you do WELL - Wan Salim, Wan Wardatul Amani (2017)
First, I will talk about my experience leading a NASA nanosatellite project from 2012 to 2014. Second, I will discuss how the work at NASA has inspired my work at International Islamic University Malaysia and how I applied the technology in my research in Malaysia. I hope that sharing my experience can empower aspiring scientist-technologists like myself to achieve significant results by applying best practices in our journey towards high-impact research and innovation, and to persevere when faced with challenges.